Transformasi Ekonomi Desa Melalui Pariwisata Lokal: Analisis Faktor Keberhasilan dan Model Pengelolaan Berkelanjutan - Muharis (JURNAL ECONOMINA, 2024)
This study was conducted with the aim of comprehensively understanding the impact of local tourism on the village economy, identifying the determining factors for success, and formulating a model for sustainable village tourism management. The research method used a qualitative case study approach in two tourist villages with data collection techniques through in-depth interviews, participant observation, and document studies of 15-20 key informants. The results revealed that local tourism has significantly transformed the village economy, marked by a 133% increase in household income, a decrease in unemployment from 15% to 6%, a 40% growth in MSMEs, and an economic multiplier effect of IDR 2.5 million for every IDR 1 million spent by tourists. Furthermore, the study successfully identified five determining factors for success and formulated a Sustainable Village Tourism Management Model integrated with five main pillars. The implementation of the model in a pilot study yielded tangible results in the form of a 40% increase in community income, a 25% decrease in tourist complaints, and a 35% increase in community participation in cultural and environmental preservation. The findings of this study recommend the importance of an integrated approach to village tourism management in order to achieve sustainable and inclusive development.